An experimental study on the lateral pressure in foam-filled wall panels with pneumatic formwork. (December 2018) - Samali, Bijan; Nemati, Saeed; Sharafi, Phezhman; Abtahi, Mojtaba; Aliabadizadeh, Yahya
Abstract: Applications of structural wall panels using flexible formwork systems have recently attracted the attention of architects and engineers. Many of such panelised systems in the market are foam-filled walls, mainly presented in the form of sandwich panels. Knowledge of cast-in-situ induced lateral pressure on the formwork is critical for the economical and safe design of flexible formwork for construction. Formwork cost, on the other hand, comprises a high proportion of the total cost of a building constructed by cast-in-situ materials. Although extensive research has been conducted on the lateral pressure of concrete formwork, the components and mechanics of the lateral pressure in foam-filled walls have not been thoroughly understood. This paper will investigate the lateral deformation, and then lateral pressure on flexible fabric formwork used for construction of polyurethane foam-filled panels. From the lateral pressure on the formwork, the tension forces in the ties are calculated by measuring the compressive force developed between the formwork edges. The results are used for design of intermediate ties for controlling the lateral deformations in an innovative foam filled panelised system, which has been designed for rapid assembly of semi-permanent buildings for post disaster housing.